“PENGENALAN APLIKASI PEMBELAJARAN ONLINE (YUK LES) BAGI PARA SISWA DI RPTRA DHARMA SUCI” - Mastan, Ignatius Adrian; Hartono, Henny; Loisa, Julia; Aristo, Julian; Honni, Honni; Carolina, Yanthi (Universitas Bunda Mulia, 2019)
One way to improve students' academic and non-academic abilities is by taking tutoring. Tutoring is an effort to achieve maximum learning outcomes in accordance with the field of interest. In the era of technological revolution 4.0, we are always demanded to be up to date on their abilities in non-academic / soft skills such as video editing, programming, dance, music, multimedia, etc. Education 4.0 should be able to provide easy access to education and mobility in learning formal and non-formal fields. The application